Predator-Prey - An Alternative Model of Stock Market Bubbles and the Business Cycle - Eduard Gracia (Intervention. Zeitschrift fuer Ökonomie / Journal of Economics, 2005)
For the last quarter of a century, the Real Business Cycle model has dominated the interpretation of business cycles in mainstream economics; yet a number of significant empirical objections to it justify exploring an alternative approach. This paper proposes to base such an approach on a predator-prey mechanism, along the lines of the classical Lotka-Volterra model for ecosystem dynamics, where agency costs play the role of the predatory activity, in a process very similar to the one proposed by the classical Austrian School interpretation of the cycle (Hayek/Schumpeter). The model is consistent with both Rational Expectations and the Efficient Markets Hypothesis, and predicts that stock market valuations will regularly present bubbles and crashes synchronised with the business cycle without this implying any irrational behaviour on the part of the investors.
Keywords: E32; 330